Pengaruh Harga, Promosi Penjualan dan Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi Pada Mixue Ice Cream & Tea Kopo Soetta, Kota Bandung) - Suenti, Sagina; Sarah, Siti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
In today's free market era, marketing is evolving at a rapid pace. Mixue Ice Cream & Tea successfully has many outlets spread across various cities in Indonesia. Mixue came to the attention of researchers, from a survey distributed to 97 people. This study aims to determine the effect of Price, Sales Promotion and Service Quality on Consumer Satisfaction (Study on Mixue Ice Cream & Tea Kopo Soetta Bandung City) with a sample size of 97 respondents. This research method is quantitative based on the philosophy of positivism, data using quantitative or statistical research instruments, with the aim of testing predetermined hypotheses. The results of the study descriptively variable Consumer Satisfaction, Price, Sales Promotion are in the good category while the service quality variable is in the unfavorable category. Partially the effect of price on customer satisfaction has a t-count value of 2.135. So it can be concluded that price has an effect on customer satisfaction. The effect of Sales Promotion on Consumer Satisfaction has a t-count value of 2.403. So it can be concluded that Sales Promotion has no effect on Consumer Satisfaction. The effect of Service Quality on Customer Satisfaction has a t-count value of 1.421. So it can be concluded that Service Quality has no effect on customer satisfaction. simultaneously shows the influence between Price, Sales Promotion, and Service Quality.